A direct-to-biology high-throughput chemistry approach to reactive fragment screening. Issue 36 (17th August 2021) - Thomas, Ross P.; Heap, Rachel E.; Zappacosta, Francesca; Grant, Emma K.; Pogány, Peter; Besley, Stephen; Fallon, David J.; Hann, Michael M.; House, David; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract : A photoreactive fragment screening platform employing direct-to-biology high-throughput chemistry (D2B-HTC) for the rapid iterative synthesis and screening of libraries of photoaffinity bits. Abstract : Methods for rapid identification of chemical tools are essential for the validation of emerging targets and to provide medicinal chemistry starting points for the development of new medicines. Here, we report a screening platform that combines 'direct-to-biology' high-throughput chemistry (D2B-HTC) with photoreactive fragments. The platform enabled the rapid synthesis of >1000 PhotoAffinity Bits (HTC-PhABits) in 384-well plates in 24 h and their subsequent screening as crude reaction products with a protein target without purification. Screening the HTC-PhABit library with carbonic anhydrase I (CAI) afforded 7 hits (0.7% hit rate), which were found to covalently crosslink in the Zn 2+ binding pocket. A powerful advantage of the D2B-HTC screening platform is the ability to rapidly perform iterative design–make–test cycles, accelerating the development and optimisation of chemical tools and medicinal chemistry starting points with little investment of resource.